ANALYSIS OF LEXICAL COHESION IN THE LEGENDS OF BATAM’S COMMUNITY: A STUDY OF DISCOURSE ANALYSIS - Rudianto, Gaguk; Johan, Mhd.; Mubarak, Zia Hisni (Asosiasi dosen IDEBAHASA KEPRI, 2023)
This study aims to reveal the use of lexical cohesion in the discourse contained in community legends in Batam. The method used in this study is a qualitative research method in which researchers conduct discourse analysis of community legends in the city of Batam. By examining further the lexical cohesion in the discourse of community legends in the city of Batam, it is hoped that this research can contribute knowledge in the study of discourse analysis based on local wisdom. The discourse presented is the legend of Batu Ampar and Sungai Jodoh. The results of the study illustrate that the most widely used device of lexical cohesion is reiteration where repetition of word forms, phrases and verbs is found. For collocations, several utterances were also found but not many. By looking at the existing discourse, the form of reiteration with repetition is one way to convey a moral message to the reader.